Everyday Life in the Culture of Surveillance - Samuelsson, Lars (Nordicom, University of Gothenburg, 2023)
Over the recent decades, the possibilities to surveil people have increased and been refined with the ongoing digital transformation of society. Surveillance can now go in any direction, and various forms of online surveillance saturate most people's lives, which are increasingly lived in digital environments. To understand this situation and nuance the contemporary discussions about surveillance - not least in the highly digitalised context of the Nordic countries - we must adopt cultural and ethical perspectives in studying people's attitudes, motives, and behaviours. The "culture of surveillance", to borrow David Lyon's term, is a culture where questions about privacy and publicness, and rights and benefits, are once again brought to the fore. This anthology takes up this challenge, with contributions from a variety of disciplinary and theoretical frameworks that discuss and shed light on the complexity of contemporary surveillance and thus problematise power relations between the many actors involved in the development and performance of surveillance culture. The contributions highlight how more and more actors and practices play a part in our increasingly digitalised society. The book is an outcome of the research project "iAccept: Soft surveillance - between acceptance and resistance", financed by the Marcus and Amalia Wallenberg Foundation. The anthology's editors are project members, all based at Umeå University, Sweden: Lars Samuelsson, associate professor of philosophy; Coppélie Cocq, professor of Sámi studies and digital humanities; Stefan Gelfgren, associate professor of sociology of religion; and Jesper Enbom, associate professor of media studies.